2021
DOI: 10.1021/jacs.1c09735
|View full text |Cite
|
Sign up to set email alerts
|

Metallization and Superconductivity in the van der Waals Compound CuP2Se through Pressure-Tuning of the Interlayer Coupling

Abstract: Emergent layered Cu-bearing van der Waals (vdW) compounds have great potentials for use in electrocatalysis, lithium batteries, and electronic and optoelectronic devices. However, many of their alluring properties such as potential superconductivity remain unknown. In this work, using CuP2Se as a model compound, we explored its electrical transport and structural evolution at pressures up to ∼60 GPa using both experimental determinations and ab initio calculations. We found that CuP2Se undergoes a semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
3
16
0
Order By: Relevance
“…26 We attribute this to the probable nanonization of NbP crystal under pressure due to the Hall-Petch-like effect. 27,28 Li et al recently reported how nanonization of particles enhances the superconductivity in the decompression process, 29 which also well-explains the results we observed in electrical-transport measurements. The pressure dependence of the axial ratio with pressure shows a discontinuous point at ∼50 GPa (as shown in Figure 3c), indicating an abnormal intrinsic change in the crystal structure of NbP.…”
supporting
confidence: 89%
“…26 We attribute this to the probable nanonization of NbP crystal under pressure due to the Hall-Petch-like effect. 27,28 Li et al recently reported how nanonization of particles enhances the superconductivity in the decompression process, 29 which also well-explains the results we observed in electrical-transport measurements. The pressure dependence of the axial ratio with pressure shows a discontinuous point at ∼50 GPa (as shown in Figure 3c), indicating an abnormal intrinsic change in the crystal structure of NbP.…”
supporting
confidence: 89%
“…In the decompression run, the R – T curve gradually degrades into semiconductor behavior, but the T c is enhanced to 5.1 K when the pressure is released to 52.6 GPa, as shown in the Figure S2. The decompression-enhanced or persistent superconductivity has also been reported on some other chalcogenides or pnictides, which is attributed to the irreversibility in grain and structure of pressurized crystals. For the second run, superconductivity with T c = 3.1 K emerges at 43.7 GPa, and the T c is enhanced to 6.2 K at 82.7 GPa, as shown in Figure c. The temperature dependence of the upper critical field at 70.5 and 82.7 GPa are depicted in Figure d.…”
supporting
confidence: 54%
“…Both experimental and theoretical studies have discussed the discontinuous change in the c / a ratio across various materials, which can be ascribed to various driving or coupling factors, encompassing structural differences, stability considerations, transitions in electronic topological phases, , and changes in elastic modulus. , The slight discrepancy between the abnormal pressure values measured by transport data (5–7 GPa) and this observation bears resemblance to the isostructural electronic transition observed in certain other materials. …”
Section: Resultsmentioning
confidence: 99%